READING TASKS IN STUDENTS’ ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL GRADE XI SEMESTER I VIEWED FROM THE TEACHERS’ PERCEPTION - mona afersa (Menara Ilmu, 2020)
This research describes the reading tasks in students' English textbook for senior high school grade XI semester I viewed from the teachers' perception.